2011
DOI: 10.1016/j.bbr.2010.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Administration of GABAB receptor positive allosteric modulators inhibit the expression of previously established methamphetamine-induced conditioned place preference

Abstract: Little is known about the role of GABAB receptors (GABABRs) in the maintenance of memories associated with using abused substances. We have embarked on a series of studies designed to determine if enhancing the efficacy of GABA-occupied GABABRs with positive allosteric modulators (PAMs) can negate previously established conditioned place preference (CPP) induced by methamphetamine. In the current study, we evaluated the effects of acute administration of GABABR PAMs, GS39783 and CGP7930. We determined that pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Alternatively, evidence in animals has consistently shown that cocaine and amphetamine inhibit GABA transmission in the striatum (Centonze et al, 2002), and enhancement of GABAergic activity reduces cocaine and methamphetamine addiction (Hip et al, 2007; Voigt et al, 2011). Since a majority of the striatal CB 1 receptors are located presynaptically on inhibitory GABAergic terminals in a position to modulate neurotransmitter release (Julian et al, 2003), a functional interaction between CB 1 and GABAergic transmission in striatum cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, evidence in animals has consistently shown that cocaine and amphetamine inhibit GABA transmission in the striatum (Centonze et al, 2002), and enhancement of GABAergic activity reduces cocaine and methamphetamine addiction (Hip et al, 2007; Voigt et al, 2011). Since a majority of the striatal CB 1 receptors are located presynaptically on inhibitory GABAergic terminals in a position to modulate neurotransmitter release (Julian et al, 2003), a functional interaction between CB 1 and GABAergic transmission in striatum cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…We have used both biased and unbiased CPP procedures in our studies with rats (Shen et al, 2006; Voigt et al, 2011b; Herrold et al, 2012) and humans (Childs and de Wit, 2009; 2011). Regarding our human studies, we first used an unbiased procedure (Childs and de Wit, 2009), assigning subjects to room-drug conditions without considering initial preferences.…”
Section: Methodological Considerations For Cpp Proceduresmentioning
confidence: 99%
“…see, Graves et al, 2012a; Herrold et al, 2009; 2012; Herzig and Schmidt, 2004; Herzig et al, 2005; Kang et al, 2008; Vidal-Infer et al, 2012; Voigt et al, 2011b; Ye et al, 2004). Testing potential therapies in the laboratory at the time of expression of conditioned responses may be more clinically relevant as treatment for human addiction processes have to be effective against conditioning that has already taken place (Brandon et al, 2011; Fox et al, 2012; Franklin et al, 2011; Langleben et al, 2012; Mogg et al, 2012).…”
Section: Conditioned Drug Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, receptor desensitization and down regulation that occur with chronic agonist administration are not observed with PAMs (Gjoni and Urwyler 2008). Similar to baclofen, GABA B R PAMs (CGP7930 and GS39783) reduce the maintenance of meth-induced CPP (Voigt et al 2011b), cocaine self-administration (Filip et al 2007;Halbout et al 2011;Smith et al 2004), cocaine- and cue-induced reinstatement of cocaine-seeking (Filip and Frankowska 2007), nicotine self-administration, and counteract nicotine-induced enhancement of brain reward function (Paterson et al 2008). Attenuation of stimulant-induced behaviors is also observed with L-type Ca 2+ channel blockers which inhibit the expression of nicotine- (Biala 2003), meth-, and cocaine- (Suzuki et al 1992) induced CPP, cocaine-induced behavioral sensitization (Martin-Iverson and Reimer 1994), the acquisition and consolidation of nicotine-induced cognitive effects (Biala et al 2013), and attenuate drug-primed reinstatement of nicotine self-administration (Biala and Budzynska 2008).…”
Section: Introductionmentioning
confidence: 99%